Building a nation: between conservation and change in brazil’s XX century - Pereira da Silva, Laura Gabrieli; de Oliveira, Fabricio Henrique (Laboratório Editorial Faculdade de Ciências e Letras, 2018)
This article aims to study the contradiction between the racialist theories of the late nineteenth century and the thirties of the 1930s to build a modern nation state and autonomous capitalist development. In other words, the present work will analyze the difficulties of thinking about the modern state in a country that had been impregnated by racialist theories that not only condemned the possibility of development but also related specifically to the Brazilian population. In order to elucidate this reflection, we turn to literature, especially Aluísio Azevedo's book O Cortiço (1890), where the construction of two black characters demonstrates how racialist theories spread in various fields of knowledge: Bertoleza, a black enslaved woman, and Rita Baiana, stereotype of the sensual mulatto. We also appeal to authors like Raimundo Nina Rodrigues, Gilberto Freyre, Florestan Fernandes and Carolina de Jesus.